2017
DOI: 10.1111/1750-3841.13730
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Free Radical Scavengers from Brazilian Green Propolis Using Off‐Line HPLC‐DPPH Assay and LC‐MS

Abstract: Brazilian green propolis is known as an appreciable natural antioxidant with abundant polyphenolic compounds. For quality control, a fingerprint-efficacy study of Brazilian green propolis was carried out in this work. Chemical fingerprints of Brazilian green propolis from 22 different sources were determined by HPLC and investigated by similarity analysis. The fingerprint-efficacy relationships between chemical fingerprint and DPPH radical-scavenging activity were established. The results showed that 14 charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 26 publications
4
32
1
1
Order By: Relevance
“…This activity is attributed mainly to the presence of flavonoids and polyphenols [ 28 ], among them, some caffeic and cinnamic acid derivatives [ 29 – 31 ]. EPP-AF® presents, unlike other propolis presentations studied, high content of artepillin C, another agent with marked antioxidant activity [ 32 ]. In this study, we showed the in vivo antioxidant effect of EPP-AF® on healthy young participants where low oxidation formation was expected and oxidative balance was preserved.…”
Section: Discussionmentioning
confidence: 99%
“…This activity is attributed mainly to the presence of flavonoids and polyphenols [ 28 ], among them, some caffeic and cinnamic acid derivatives [ 29 – 31 ]. EPP-AF® presents, unlike other propolis presentations studied, high content of artepillin C, another agent with marked antioxidant activity [ 32 ]. In this study, we showed the in vivo antioxidant effect of EPP-AF® on healthy young participants where low oxidation formation was expected and oxidative balance was preserved.…”
Section: Discussionmentioning
confidence: 99%
“…In the same in vitro studies, the antioxidant capacity of propolis extracts was found to be similar to that of the synthetic antioxidant butylated hydroxytoluene or ascorbic acid [ 4 , 20 ]. Importantly, the antioxidant capacity of propolis is dependent on its content, but the studies aiming at finding the distinct relationships between these two parameters are not consistent [ 3 , 35 , 36 ]. In general, according to the literature data, the total phenolic content of propolis extracts ranged from about 30 to 200 mg of gallic acid equivalents (GAE)/g of dry weight, and the flavonoid content ranged from about 30 to 70 mg of quercetin equivalents (QE)/g, whereas DPPH free radical-scavenging activity ranged from about 20 to 190 μ g/mL [ 3 , 19 , 20 , 31 , 35 , 36 , 38 ].…”
Section: Propolis: “Bee Glue”mentioning
confidence: 99%
“…The phenolic compounds, but the different ones than the flavonoids, are believed to be responsible for the antioxidant activity of Brazilian propolis. According to Zhang et al [ 36 ], 3,4,5-tricaffeoylquinic acid, 3,5-dicaffeoylquinic acid, 4,5-dicaffeoylquinic acid, and artepillin C seem to be responsible for the strong antioxidant activity of Brazilian green propolis. Unlike in the case of Brazilian propolis, the antioxidant activity of poplar propolis appears to be largely influenced by both total polyphenol and total flavonoid contents [ 3 , 34 , 38 ].…”
Section: Propolis: “Bee Glue”mentioning
confidence: 99%
“…Then, 20 µL of the mixture was injected into the HPLC and analyzed as described above. A blank control of carob extracts with the same volume of methanol was also analyzed [23].…”
Section: Hplc Coupled On a Pre-column Dpph Assaymentioning
confidence: 99%